Determinants of Competitor’s Response Time to the New Product in the Market of Nepal - Sharma, Bed Nath (Journal of Nepalese Business Studies, 2007)
This study is concerned with competitor’s response time determinants to a new consumer product in Nepalese market. Products are in high competitive situation. New–to-the-world product is facing more competition complexities. Channels, market research, sales force and public opinions are the main source to get the market information of new products. Consultant’s service is main helping hand to increase competitive strength. Financial and non-financial measures are applied to increase the competitive ability. Both qualitative and quantitative methods are in use to measure competitiveness of new products. The competitor’s response time to most of the new products is less than six months after commercialization. Types of users are also in focus while developing the new products. Cutthroat competition is emerging in the market and firms are not able to defend fairly. Journal of Nepalese Business Studies Vol.2(1) 2005 pp.33-40